Neotectonic structures and modern geodynamics of the middle flow region of the Don river (the territory of the Novovoronezh nuclear power plant) - V. M. Makeev; E. A. Pikulik; A. S. Guseltsev (Известия высших учебных заведений: Геология и разведка)
Background. Structural and geodynamic studies are conducted in the region of the middle flow of the Don river.Aim. An identification and evaluation of neotectonic structures, determination of geodynamic conditions for their formation and an analysis of intensive exogenous geological processes in connection with the need to ensure the safety of the Novovoronezh nuclear power plant (NPP) located in this area, the largest in the central part of the Eastern European platform.Materials and methods. According to the concept of deep geodynamic systems, the lithological, structural-geomorphological and neotectonic conditions of the territory were studied. Field observations and publications based on geological survey data were the factual material for the studies.Results. Various types of uplifts and troughs, geodynamically active zones and lineaments were identified. The formation of structures is associated with deep (intracortical) stresses of compression and tension, under the influence of which the tectonic-gravity and suffosion-karst processes negative for the territory of the nuclear power plant are activated. Among the ancient Precambrian faults of the crystalline basement, the latitudinal Sudzhen-Ikorets and submeridional Semiluki-Lipetsky faults are active. The latter is considered as a geodynamically active zone. At the NPP site and in its vicinity, the zones of increased fracturing and permeability were identified, which is consistent with the buried forms of the relief — paleo-reliefs of the Don river and its tributaries. These zones are found to be deeply embedded in the Cretaceous and Devonian carbonate rocks, which is the reason for the increased leaching of these rocks and the removal of fine particles from the fluvioglacial strata. A quantitative assessment of summary and step-by-step amplitudes and speeds of neotectonic movements was carried out.Conclusion. The territory of the Novovoronezh NPP is geodynamically calm, the movement speeds (both calculated and according to instrumental measurements) are relatively low; however, these movements activate exogenous processes, which in turn negatively affect the stability of the Novovoronezh NPP site.